A fuzzy assessment method to airport waste management: A case study of Congonhas Airport, Brazil - Santos, Alexsander José dos [UNESP]; Mancini, Sandro Donnini [UNESP]; Frutuoso Roveda, José Arnaldo [UNESP]; Ewbank, Henrique; Roveda, Sandra Regina Monteiro Masalskiene [UNESP] (Elsevier, 2020)
This study presents a fuzzy mathematical model to support and evaluate airport waste management. The model generates a waste management index, composed of three dimensions, and it was applied in a case study of Congonhas Airport, located in Brazil. In addition to the mathematical model, the nonparametric Mann-Kendall test was applied to verify the existence of bias in the obtained results. The results showed that there is a concern on the part of the airport regarding waste management, reflected in the Fuzzy Waste Management Index (FWMI) results. They also indicated that there was an improvement in waste management in 2015 compared to 2014, resulting from increased accounting for recyclables and awareness of the airport community. The developed model proved to be an important tool to support the decision making of airport managers, including aspects related to waste management steps, and there may be adjustments that may be made to include new indicators.
Keywords: Airport waste; Airports; Fuzzy modeling; Solid waste management; Systems based on fuzzy rules